Transmutation of Sweat Glands - Eccrine Porocarcinoma - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2019)
Initially described by Pinkus and Mehregan in 1963 as an epidermotropic eccrine carcinoma, eccrine porocarcinoma cogitates an exceptional sweat gland malignancy. Eccrine porocarcinoma was adapted as a nomenclature by Mishisma and Morikoin in 1969. The neoplasm is a malignant analogue of eccrine poroma which is a benign tumour of intra-dermal sweat glands. Eccrine porocarcinoma is an invasive malignancy of eccrine sweat gland with an acrosyringial genesis. Nomenclature includes epidermotropic eccrine carcinoma, eccrine poroepithelioma, malignant hidroacanthoma simplex, malignant intra-epidermal eccrine poroma, malignant eccrine poroma, malignant syringoacanthoma and dysplastic poroma (1,2). Sweat gland carcinoma are categorized into subgroups with the classical eccrine porocarcinoma or eccrine adenocarcinoma as a prevalent subcategory. Lesions are enlisted as Classic type eccrine adenocarcinoma ( eccrine porocarcinoma). Syringoid eccrine carcinoma Microcystic adnexal carcinoma Mucinous eccrine carcinoma Muco-epidermoid carcinoma Adenoid cystic carcinoma Aggressive digital papillary adenoma/adenocarcinoma
Keywords: Mucinous eccrine carcinoma